Lipoprotein-associated phospholipase A(2) and future risk of subclinical disease and cardiovascular events in individuals with type 2 diabetes: the Cardiovascular Health Study - Nelson, T. L. (2010)
AIMS/HYPOTHESIS: Type 2 diabetes is an established risk factor for cardiovascular disease (CVD). This increased risk may be due in part to the increased levels of inflammatory factors associated with diabetes. Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) is a risk marker for CVD and has pro-inflammatory effects in atherosclerotic plaques. We therefore sought to determine whether Lp-PLA(2) levels partially explain the greater prevalence of subclinical CVD and greater incidence of CVD outcomes associated with type 2 diabetes in the Cardiovascular Health Study. METHODS: We conducted a cross-sectional and prospective study of 4,062 men and women without previous CVD from the Cardiovascular Health Study (1989 to 2007). Lp-PLA(2) mass and activity were measured in baseline plasma. Subclinical disease was determined at baseline and incident CVD was ascertained annually. We used logistic regression for cross-sectional analyses and Cox proportional hazards models for incident analyses. RESULTS: At baseline, Lp-PLA(2) mass did not differ significantly by type 2 diabetes status; however, Lp-PLA(2) activity was significantly higher among type 2 diabetic individuals. Baseline subclinical disease was significantly associated with baseline diabetes and this association was similar in models unadjusted or adjusted for Lp-PLA(2) (OR 1.68 [95% CI 1.31–2.15] vs OR 1.67 [95% CI 1.30–2.13]). Baseline type 2 diabetes was also significantly associated with incident CVD events, including fatal CHD, fatal myocardial infarction (MI) and non-fatal MI in multivariable analyses. There were no differences in these estimates after further adjustment for Lp-PLA(2) activity. CONCLUSIONS/INTERPRETATION: In this older cohort, differences in Lp-PLA(2) activity did not explain any of the excess risk for subclinical disease or CVD outcomes related to diabetes.